ENGAGING STUDENTS IN ONLINE READING GAMES: A STUDENT-CENTERED LEARNING PERSPECTIVE - Prima Purbasari; Iffatunnida Iffatunnida; Urwatus Silvia Rahmah Silvia Rahmah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
2020 might be unforgettable for teachers since they need to face the challenging teaching situation in the ruinous Covid-19 pandemic. To deliver the lesson, teachers need varied online applications to reach their students. Furthermore, they need more online media to ensure the students grasp what they need to achieve as a learning outcome. Online games are used in this study as the supportive learning tool after lecturing session about Reading Strategies. Furthermore, it is the tool to engage students to practice the student-centered learning so that they will be autonomous learners. There are four games used in this study i.e. Main Idea Millionaire, Main Idea Storm, Context Clues, and Scanning Skimming games, which are provided in three different websites. This is a qualitative phenomenological study expecting to capture details and experience of students and then to describe the meaning of the findings based on the subjects’ individual experience. The study was conducted in Universitas Islam Negeri Maulana Malik Ibrahim Malang, exactly at Architectural Engineering Department. Based on the findings, students thought that online reading games helped them to visualize the context of particular texts because of its good animation and sound effects. Students, in teacher’s evaluation, became more active in engaging themselves in the class discussion after having several activities of playing the online reading games. They said that they could easily play the games over and over anytime. This study proves that the employed online games can boost students’ confidence and encourage them to be active in the teaching and learning situation.